ПРИНЦИПЫ ОТБОРА ЛИНГВИСТИЧЕСКИХ ТЕРМИНОВ ДЛЯ ОБУЧЕНИЯ ПЕРЕВОДУ СТУДЕНТОВ-ФИЛОЛОГОВ (НА МАТЕРИАЛЕ НЕМЕЦКОГО И АНГЛИЙСКОГО ЯЗЫКА) - Володина, Татьяна (Acta Neophilologica, 2018)
The article represents the author’s attempt to systematize the selection principles of the linguistic terms for optimizing the learning process of translation for the Germanic Philology Faculty. The author analyzes in detail the criteria of systematicity of the linguistic terminology on the material of the English and German language scientific dictionaries and monographs; highlights the basic construction principles of the linguistic terms system and the concepts they denote.